Analysis Of Currency Vitamin C In Papaya Fruit (Carica Papaya L.) - Ifa Nurhasanah (Jurnal EduHealth, 2023)
Hawaiian papaya fruit has nutritional content that can nourish the human body. One of the nutrients contained in this fruit is vitamin C. The benefit of vitamin C is to help the absorption of iron, thus avoiding anemia. The purpose of the study was to determine and analyze the levels of vitamin C in Hawaiian papaya fruit. The method used in the study was to use qualitative and quantitative analysis tests with UV-Vis spectrophotometric devices conducted at the Sucofindo Laboratory in Surabaya in September 2022-January 2023. The results of the qualitative analysis test state that Hawaiian papaya fruit has vitamin C content, while the results of the quantitative analysis test state that the level of vitamin C content in papaya is 726 mg/100 g. The conclusion of this study is that Hawaiian papaya fruit can be consumed by the community because the level of vitamin C content in this fruit can meet nutritional needs in the body, especially can increase hemoglobin levels in the blood.